2013
DOI: 10.1155/2013/430290
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cells from Basic Research to Potential Clinical Applications in Cancer

Abstract: The human induced pluripotent stem cells (hiPSCs) are derived from a direct reprogramming of human somatic cells to a pluripotent stage through ectopic expression of specific transcription factors. These cells have two important properties, which are the self-renewal capacity and the ability to differentiate into any cell type of the human body. So, the discovery of hiPSCs opens new opportunities in biomedical sciences, since these cells may be useful for understanding the mechanisms of diseases in the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…Declared activation of tumor-specific CTLs is the main goal of cancer immunotherapy; so, adoptive transfer of tumor-specific T-cells is one of the effective therapeutic approaches for fighting against many types of malignancies [ 55 57 ]. The isolation of tumor-specific T-cells from a cancer patient, in vitro preparation (activation and expansion), and transfusion of these T-cells to the patient are basic steps of adaptive immunotherapy with T-cell [ 55 ], although there are some problems with this approach, for example, the low number of antigen-specific T-cells and senescence of these activated cells [ 55 , 56 , 58 ]. Then, iPSC technology can be used to improve the efficacy of adoptive cell transfer immunotherapy (ACT).…”
Section: Ipsc Applications In Stimulation Of Antitumor Immune Respmentioning
confidence: 99%
“…Declared activation of tumor-specific CTLs is the main goal of cancer immunotherapy; so, adoptive transfer of tumor-specific T-cells is one of the effective therapeutic approaches for fighting against many types of malignancies [ 55 57 ]. The isolation of tumor-specific T-cells from a cancer patient, in vitro preparation (activation and expansion), and transfusion of these T-cells to the patient are basic steps of adaptive immunotherapy with T-cell [ 55 ], although there are some problems with this approach, for example, the low number of antigen-specific T-cells and senescence of these activated cells [ 55 , 56 , 58 ]. Then, iPSC technology can be used to improve the efficacy of adoptive cell transfer immunotherapy (ACT).…”
Section: Ipsc Applications In Stimulation Of Antitumor Immune Respmentioning
confidence: 99%
“…Activation of transcription factors and modification of chromatin regulators may result in the remodeling of epigenetic status and refueling of tumorigenicity in these reprogrammed cancer cells. However, until now, studies that focused on cancer cell reprogramming [58][59][60][61][62][63][64][65][66][67] are contradictory; some studies reported increased tumor progression whereas others showed cellular reprogramming has a treatment potential for cancer:…”
Section: A Connecting Tumorigenesis and Cellular Reprogrammingmentioning
confidence: 99%
“…The ability to define the initiating molecular mechanisms of human cataract formation—and, therefore, effective treatments to inhibit or delay cataract progression—has largely been hampered by the lack of access to functional human lens tissue at the initial stages of cataract formation. The ability of human pluripotent stem (PS) cells to (i) self-renew and (ii) differentiate into any cell type of the body, means human PS cells can provide a large-scale source of normal or diseased human cells for research [1,2,3,4]. Consequently, human PS cells are enabling new research approaches into human cell and tissue development, elucidation of molecular disease mechanisms, drug discovery and toxicity assessments, and investigation of candidate cell-based therapies.…”
Section: Introductionmentioning
confidence: 99%